Perioperative Change of High‐Sensitive Cardiac Troponin I Concentration in Cats According to Three Different Anaesthesia Protocols - Safak, Tarik; Yılmaz‐Koç, Oznur; Karakaya‐Bilen, Ebru (Wiley, 2024)
ABSTRACTBackgroundCardiac troponin I, a particular biomarker, is released into the bloodstream in response to myocardial injury.ObjectivesTo evaluate perioperative changes in high‐sensitivity cardiac troponin I (hs‐cTnI) concentration during ovariohysterectomy in cats undergoing three different anaesthesia protocols.Methods Twenty‐one female mixed‐breed cats owned by clients aged (2.2 ± 0.7 years) and weight (3.2 ± 0.5 kg) were included in our study. The cats were divided into three groups: propofol–isoflurane (PI) group (n = 7), xylazine–ketamine (XK) group (n = 7) and xylazine–isoflurane (XI) group (n = 7). After pre‐anaesthetic propofol (6 mg/kg IV) was administered to cats in Group PI, a mask was placed, and anaesthesia was maintained with 3.0% isoflurane in oxygen. Cats in Group XK underwent general anesthetization with xylazine hydrochloride (2 mg/kg IM) and, 10 min later, ketamine hydrochloride (10 mg/kg IM). Cats in Group XI were administered xylazine hydrochloride (2 mg/kg IM), and then anaesthesia (3.0% isoflurane and oxygen) was continued with a mask. Blood samples were collected from all cats; preoperatively and postoperatively at 0 and 12 h (Pre‐, Post‐0 h and Post‐12 h, respectively). Serum hs‐cTnI concentrations were measured with the Advia Centaur TnI‐Ultra.ResultsIn all 21 cats, hs‐cTnI concentration increased at Post‐0 h and 12 h measurement points compared to Pre‐. In the XK group, hs‐cTnI concentrations exhibited a significant increase at the Post‐0 h (51.30 ng/L) and Post‐12 h (157.70 ng/L) time points compared to Pre‐ (6.70 ng/L) (p < 0.05).ConclusionsThe XK group increased the concentration of hs‐cTnI more than other protocols. In the PI group, the increase in hs‐cTnI concentrations at Post‐0 and 12 h increased less than the other two groups (p < 0.05). The PI group was found to induce less myocardial damage.
Keywords: Xylazine; cardiac troponin I; propofol; Isoflurane; xylazine hydrochloride; Veterinary medicine; Ovariectomy; Troponin I; cat; ketamine hydrochloride; Anesthesia, General; Hysterectomy; isoflurane; SF600-1100; Anesthetics, Inhalation; Cats; Animals; Original Article; Female; Ketamine; Anesthesia; Perioperative Period; Propofol; Anesthetics, Intravenous